PENGARUH PENGOLAHAN BUAH MANGGA MANALAGI SEGAR (Mangifera indica L.) MENJADI MANISAN MANGGA KERING TERHADAP KADAR VITAMIN C - Choriun Niswah; Elfira Rosa Pane; Ela Irmawati (Biota, 2016)
Manalagi  mango fruit (Mangifera indica L)  is one of fruits containing lots of vitamin C and it can be processed into mango dried candied. This research is aimed to determine the levels of vitamin C in the mango dried candied that is sold in modern markets in Palembang and to contribute about biology subject at senior high school / madrasah aliyah. The methods of this study is the idiometri test. This study uses the form control manalagi fresh mango fruit. Samples are taken from several modern market in Palembang city by using simple random sampling method. The result of the test iodimetri along with qualitative test on sample 4 and 6 do not contain vitamin C, while in sample 1, 2, 3, and 5 contain vitamin C which is an average of the levels of vitamin C in the sample 1 of 4.78 mg / 100 gr, 2 sample of 3.66 mg / 100 g, 3 sample of 2.64 mg / 100 g, 5 sample of 5.22 mg / 100 g. This shows manalagi fresh mango fruit is processed into dried candied still have high levels of vitamin C which is quite high when compared to the levels of vitamin C in control in the amount of 3.08 mg / 100 g. Contributing to education that is presented in the form of lesson plans, worksheets and posters. The contribute of  biology subject to the education is presented in the form of  lesson plans, worksheets and posters